Current Concepts in Neuroendocrine Disruption - León-Olea, Martha (2014)
In the last few years, it has become clear that a wide variety of environmental contaminants have specific effects on neuroendocrine systems in fish, amphibians, birds and mammals. While it is beyond the scope of this review to provide a comprehensive examination of all of these neuroendocrine disruptors, we will focus on select representative examples. Organochlorine pesticides bioaccumulate in neuroendocrine areas of the brain that directly regulate GnRH neurons, thereby altering the expression of genes downstream of GnRH signaling. Organochlorine pesticides can also agonize or antagonize hormone receptors, adversely affecting crosstalk between neurotransmitter systems. The impacts of polychlorinated biphenyls are varied and in many cases subtle. This is particularly true for neuroedocrine and behavioral effects of exposure. These effects impact sexual differentiation of the hypothalamic-pituitary-gonadal axis, and other neuroendocrine systems regulating the thyroid, metabolic, and stress axes and their physiological responses. Weakly estrogenic and anti-androgenic pollutants such as bisphenol A, phthalates, phytochemicals, and the fungicide vinclozolin can lead to severe and widespread neuroendocrine disruptions in discrete brain regions, including the hippocampus, amygdala, and hypothalamus, resulting in behavioral changes in a wide range of species. Behavioral features that have been shown to be affected by one or more these chemicals include cognitive deficits, heightened anxiety or anxiety-like, sociosexual, locomotor, and appetitive behaviors. Neuroactive pharmaceuticals are now widely detected in aquatic environments and water supplies through the release of wastewater treatment plant effluents. The antidepressant fluoxetine is one such pharmaceutical neuroendocrine disruptor. Fluoxetine is a selective serotonin reuptake inhibitor that can affect multiple neuroendocrine pathways and behavioral circuits, including disruptive effects on reproduction and feeding in fish. There is growing evidence for the association between environmental contaminant exposures and diseases with strong neuroendocrine components, for example decreased fecundity, neurodegeneration, and cardiac disease. It is critical to consider the timing of exposures of neuroendocrine disruptors because embryonic stages of central nervous system development are exquisitely sensitive to adverse effects. There is also evidence for epigenetic and transgenerational neuroendocrine disrupting effects of some pollutants. We must now consider the impacts of neuroendocrine disruptors on reproduction, development, growth and behaviors, and the population consequences for evolutionary change in an increasingly contaminated world. This review examines the evidence to date that various so-called neuroendocrine disruptors can induce such effects often at environmentally-relevant concentrations.